Taxa, turnover and taphofacies: a preliminary analysis of facies-assemblage relationships in the Ediacara Member (Flinders Ranges, South Australia). Issue 6 (17th August 2020) - Reid, L. M.; Holmes, J. D.; Payne, J. L.; García-Bellido, D. C.; Jago, J. B.
Abstract: The Ediacara Member of the Flinders Ranges (South Australia) preserves body and trace fossils of the Ediacara biota. Fossils span five lithofacies representative of a range of shallow-marine environments and are preserved as in situ and transported material. Previous work has demonstrated a relationship between paleoenvironment and taxa at the Nilpena fossil site. We expand the analysis to include facies-taxa data from a further nine localities across the Flinders Ranges to assess if the taxa–paleoenvironment relationship is site specific or valid at a regional scale. The new analysis demonstrates that the distribution of taxa within the lithofacies, as a proxy for paleoenvironment, is non-random. This preliminary analysis presents a beta diversity-like spatial turnover across the range of shallow marine Ediacaran environments, and demonstrates taxonomic assemblages are specific to given paleoenvironmental zones. These assemblages are consistent over a broad spatial extent and also a presumed temporal distribution. This specificity indicates that a marked sensitivity to environmental parameters was present in these communities, as demonstrated by the non-random distribution of taxa and spatial turnover of biotic assemblage throughout the gradational environments of the Ediacara Member. This study highlights the variability and heterogeneity that is a characteristic of shallow marine settings, and offers a novel approach to the future investigation of the relationship between Ediacaran environments and taxa assemblages.